2022
DOI: 10.1136/openhrt-2021-001814
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction in people with HIV without known cardiovascular risk factors in Western Kenya

Abstract: ObjectivesDiastolic dysfunction (DD) has been reported to be highly prevalent in people living with HIV (PLWH) on antiretroviral therapy (ART) leading to the hypothesis that it may be an early marker of myocardial disease. Our objective was to evaluate the prevalence of DD in people living with human immunodeficiency virus without known history of diabetes or hypertension in Western Kenya.MethodsIn this cross-sectional study in western Kenya, 110 PLWH on ART and without known diabetes or hypertension were matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Echocardiographic studies have reported a high prevalence of diastolic dysfunction, ranging from 40 to 50%, in ALHIV [9,11,12]. Nevertheless, newer reports found that in individuals without cardiovascular risk factors such as diabetes or hypertension, diastolic dysfunction was almost absent [13]. In our study, the prevalence was also lower (21%), and it could be explained by the low incidence of cardiovascular risk factors in our population.…”
Section: Discussioncontrasting
confidence: 52%
“…Echocardiographic studies have reported a high prevalence of diastolic dysfunction, ranging from 40 to 50%, in ALHIV [9,11,12]. Nevertheless, newer reports found that in individuals without cardiovascular risk factors such as diabetes or hypertension, diastolic dysfunction was almost absent [13]. In our study, the prevalence was also lower (21%), and it could be explained by the low incidence of cardiovascular risk factors in our population.…”
Section: Discussioncontrasting
confidence: 52%
“… 26–28 A recent cross-sectional study from Kenya found a low rate of diastolic dysfunction in people living with HIV and a similar rate as compared with age and sex-matched individuals without HIV; however, individuals with HIV did have significantly higher LV mass index and left atrial volume. 29 None of the participants in this study had hypertension, limiting comparisons with our study population.…”
Section: Discussionmentioning
confidence: 90%
“…Proposed mechanisms for this include chronic inflammation and immune activation, even in the setting of viral suppression23–25 and increased pericardial fat density,21 which is common in people living with HIV and has been associated with coronary artery calcification and myocardial infarction 26–28. A recent cross-sectional study from Kenya found a low rate of diastolic dysfunction in people living with HIV and a similar rate as compared with age and sex-matched individuals without HIV; however, individuals with HIV did have significantly higher LV mass index and left atrial volume 29. None of the participants in this study had hypertension, limiting comparisons with our study population.…”
Section: Discussionmentioning
confidence: 99%
“…However, among some studies of PLWH in African nations, diastolic dysfunction is much less prevalent (1–7%) [32,33] and similar by HIV serostatus [32,33], perhaps due to younger participants, few traditional cardiac risk factors and yet unidentified differences in environmental factors. Nonetheless, left ventricular mass was higher among these younger African PLWH compared to uninfected controls which may predispose to future diastolic dysfunction [32,33]. Risk factors for left ventricular hypertrophy include CD4 count ≤200 cells/mm 3 , lack of viral suppression [29], and later initiation of ART [33], whereas lower CD4 count [29] and more severe HIV disease [33] correlate with diastolic dysfunction.…”
Section: Subclinical Disease Measures and Risk Of Heart Failure In Pe...mentioning
confidence: 99%
“…Prevalent diastolic dysfunction ranges from 22–37% among cohorts of middle-aged PLWH [10,20 ▪ ,29]. However, among some studies of PLWH in African nations, diastolic dysfunction is much less prevalent (1–7%) [32,33] and similar by HIV serostatus [32,33], perhaps due to younger participants, few traditional cardiac risk factors and yet unidentified differences in environmental factors. Nonetheless, left ventricular mass was higher among these younger African PLWH compared to uninfected controls which may predispose to future diastolic dysfunction [32,33].…”
Section: Subclinical Disease Measures and Risk Of Heart Failure In Pe...mentioning
confidence: 99%